Application of 5-fluorobenzoxazole-2-mercaptan, solar cell and preparation method of 5-fluorobenzoxazole-2-mercaptan
By using 5-fluorobenzoxazole-2-thiol as a passivator in perovskite solar cells, the problem of unsatisfactory stability of perovskite solar cells is solved, and the effect of improving photoelectric conversion efficiency and stability is achieved.
Patent Information
- Application Number
- CN202510091705.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-05-02
AI Technical Summary
The stability of perovskite solar cells is not ideal, and the passivation effect of existing passivating agents is not good enough, resulting in the impact of battery performance.
5-fluorobenzoxazole-2-thiol is used as the passivating agent for the perovskite layer, and the passivating layer is formed by heat treatment to improve the stability and charge transport capability of the perovskite layer.
Effectively reduce the defect density of the perovskite layer, improve the photoelectric conversion efficiency, open circuit voltage and short circuit current, and enhance the stability of the battery to environmental factors.
Smart Images

Figure CN119923179A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy, and in particular to solar cells. Background Art
[0002] Perovskite materials have excellent optical and electronic properties, with high absorption coefficient and charge carrier mobility, long carrier diffusion distance and adjustable band gap. At present, perovskite-based solar cells have made great progress in photoelectric conversion efficiency, and the photoelectric conversion efficiency is close to that of commercialized silicon-based solar cells. Perovskite solar cells also have the advantages of low cost, simple preparation process, high photoelectric conversion efficiency, etc., showing great development potential. However, perovskite battery devices are sensitive to light and water, and their stability is not ideal. Due to the migration of halide ions and metal ions, the contact effect of precious metals such as silver will destroy the stability of the battery. In perovskite solar cells, high-density defects appear in the body and grain boundaries of the perovskite film, which will inevitably deteriorate the device performance. Surface passivation treatment of perovskite film by passivator is an effective method to reduce the recombination and energy loss at the interface. However, in the prior art, the stability of the perovskite film after passivation treatment is still not ideal, and the passivation effect of the passivator still needs to be improved. Summary of the invention
[0003] The embodiments of the present application provide an application of 5-fluorobenzoxazole-2-thiol, a solar cell and a preparation method thereof to solve the technical problem that the passivation effect of the passivator is not good enough.
[0004] In a first aspect, an embodiment of the present application provides an application of 5-fluorobenzoxazole-2-thiol, wherein the 5-fluorobenzoxazole-2-thiol is applied as a passivator for a perovskite layer in a perovskite solar cell.
[0005] In a second aspect, an embodiment of the present application provides a solar cell, the solar cell comprising:
[0006] substrate;
[0007] An electron transport layer disposed on the substrate;
[0008] a perovskite layer disposed on the electron transport layer;
[0009] a passivation layer disposed on the perovskite layer;
[0010] A hole transport layer is provided on the passivation layer,
[0011] An electrode disposed on the hole transport layer,
[0012] Wherein, the material of the passivation layer includes 5-fluorobenzoxazole-2-thiol.
[0013] In some embodiments of the present application, the substrate is ITO conductive glass or FTO conductive glass; and / or,
[0014] The material of the electron transport layer includes SnO2, TiO2, C 60 , C 60 at least one of the derivatives; and / or,
[0015] The thickness of the electron transport layer is 10 to 50 nm; and / or,
[0016] The thickness of the perovskite layer is 300-800 nm; and / or,
[0017] The thickness of the passivation layer is 5 to 30 nm; and / or,
[0018] The material of the hole transport layer includes at least one of Spiro-Ometad, nickel oxide, copper oxide, and PTAA; and / or,
[0019] The thickness of the hole transport layer is 10 to 50 nm; and / or,
[0020] The material of the electrode includes at least one of Au, Ag and Cu.
[0021] In some embodiments of the present application, the thickness of the electron transport layer is 20 to 40 nm; and / or,
[0022] The thickness of the passivation layer is 10 to 20 nm; and / or,
[0023] The thickness of the hole transport layer is 20-40 nm.
[0024] In a third aspect, an embodiment of the present application provides a method for preparing a solar cell, the method comprising the following steps:
[0025] providing a substrate;
[0026] preparing an electron transport layer on the substrate;
[0027] preparing a perovskite layer on the electron transport layer;
[0028] coating a passivation solution on the perovskite layer, wherein the solute of the passivation solution includes 5-fluorobenzoxazole-2-thiol;
[0029] Performing a first heat treatment on the passivation solution on the perovskite layer so that the passivation solution forms a passivation layer;
[0030] preparing a hole transport layer on the passivation layer,
[0031] An electrode is prepared on the hole transport layer to obtain the solar cell.
[0032] In some embodiments of the present application, the step of preparing a perovskite layer on the electron transport layer comprises the following steps:
[0033] coating an inorganic salt solution on the electron transport layer;
[0034] coating an organic salt solution on the inorganic salt solution;
[0035] The inorganic salt solution and the organic salt solution are subjected to a second heat treatment so that the organic salt solution and the inorganic salt solution react to form a perovskite layer.
[0036] Wherein, the organic salt is at least one of FAI, MAI, MACl, FABr and MABr, and the inorganic salt is at least one of PbI2, PbBr2, PbCl2, CsBr, CsI and SnI2.
[0037] In some embodiments of the present application, the temperature of the first heat treatment is 50-150° C.; and / or,
[0038] The first heat treatment lasts for 1 to 10 minutes; and / or,
[0039] The temperature of the second heat treatment is 100-150° C.; and / or,
[0040] The second heat treatment time is 10 to 15 minutes.
[0041] In some embodiments of the present application, the temperature of the first heat treatment is 70-100° C.; and / or,
[0042] The first heat treatment time is 3 to 5 minutes.
[0043] In some embodiments of the present application, the solvent of the passivation solution is isopropanol; and / or,
[0044] The concentration of 5-fluorobenzoxazole-2-thiol in the passivation solution is 0.5-5 mg / ml.
[0045] In some embodiments of the present application, the concentration of 5-fluorobenzoxazole-2-thiol in the passivation solution is 0.5-2 mg / ml.
[0046] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0047] The 5-fluorobenzoxazole-2-thiol provided in the embodiment of the present application can simultaneously improve the stability of the molecule, form a strong chemical bond with the perovskite layer, optimize the interface energy level matching, and improve the electron or hole transmission capacity of the interface, so it can effectively reduce and fill the surface defects of the perovskite layer and reduce the defect density of the perovskite layer. This single molecule design reduces the mixing uniformity problem that may exist when multiple small molecules are used in combination, avoids the problem of inconsistent performance of the interface layer, simplifies the preparation process, reduces the complexity and cost of operation, and improves repeatability and industrial feasibility. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0049] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0050] Figure 1 The voltage-current curve of the case where 5-fluorobenzoxazole-2-thiol was added and the control group provided in the examples of the present application;
[0051] Figure 2 This is a box plot of battery performance for the battery with 5-fluorobenzoxazole-2-thiol added and the control group provided in the examples of the present application. DETAILED DESCRIPTION
[0052] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0053] Unless otherwise specified, the terms used herein should be understood as commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which this application belongs. In the event of a conflict, this specification takes precedence.
[0054] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0055] The existing passivators for perovskite solar cells have the technical problem of insufficient passivation effect.
[0056] The technical solution provided by the embodiments of the present application is to solve the above technical problems, and the overall idea is as follows:
[0057] In a first aspect, an embodiment of the present application provides an application of 5-fluorobenzoxazole-2-thiol, wherein the 5-fluorobenzoxazole-2-thiol is applied as a passivator for a perovskite layer in a perovskite solar cell.
[0058] As an organic compound, 5-fluorobenzoxazole-2-thiol has a unique chemical structure and properties, which can interact with defects or impurities in the perovskite layer, thereby effectively reducing or eliminating the adverse effects of these defects on battery performance. Specifically, it may achieve the passivation effect through the following mechanism: 5-fluorobenzoxazole-2-thiol molecules can penetrate into the tiny defects of the perovskite layer and fill these defects through chemical bonding, thereby reducing scattering and recombination losses during charge transfer. Through passivation treatment, 5-fluorobenzoxazole-2-thiol can change the surface properties of the perovskite layer, making it smoother and more uniform, which is conducive to the transfer and collection of charges. The introduction of 5-fluorobenzoxazole-2-thiol can also improve the stability of the perovskite layer to environmental factors such as humidity, light intensity, and temperature, thereby extending the service life of the battery. 5-Fluorobenzoxazole-2-thiol has the following application advantages:
[0059] 1. Compared with traditional passivators, 5-fluorobenzoxazole-2-thiol has stronger passivation ability and higher selectivity, and can more effectively reduce defects and impurities in the perovskite layer. 2. By optimizing the passivation conditions, the introduction of 5-fluorobenzoxazole-2-thiol can significantly improve the key performance parameters of perovskite solar cells, such as photoelectric conversion efficiency, open circuit voltage and short circuit current. 3. The passivation effect of 5-fluorobenzoxazole-2-thiol can also enhance the stability of perovskite solar cells to environmental factors such as humidity, light intensity, and temperature, so that they can still maintain a high performance level under various harsh conditions.
[0060] The present application applies 5-fluorobenzoxazole-2-thiol to the passivation agent of the perovskite layer in the perovskite solar cell. 5-fluorobenzoxazole-2-thiol contains phenyl, thiol and halogen atoms at the same time, which can simultaneously improve the stability of the molecule, form a strong chemical bond with the perovskite layer, optimize the interface energy level matching, and improve the electron or hole transport capacity of the interface, so it can effectively reduce and fill the surface defects of the perovskite layer and reduce the defect density of the perovskite layer. This single molecule design reduces the mixing uniformity problem that may exist when multiple small molecules are used in combination, avoids the problem of inconsistent performance of the interface layer, simplifies the preparation process, reduces the complexity and cost of operation, and improves repeatability and industrial feasibility.
[0061] In a second aspect, an embodiment of the present application provides a solar cell, the solar cell comprising:
[0062] substrate;
[0063] An electron transport layer disposed on the substrate;
[0064] a perovskite layer disposed on the electron transport layer;
[0065] a passivation layer disposed on the perovskite layer;
[0066] A hole transport layer is provided on the passivation layer,
[0067] An electrode disposed on the hole transport layer,
[0068] Wherein, the material of the passivation layer includes 5-fluorobenzoxazole-2-thiol.
[0069] The solar cell is realized based on the application of 5-fluorobenzoxazole-2-thiol described in any embodiment of the first aspect. The specific implementation of the solar cell can refer to the above embodiments and common knowledge in the art. Since the solar cell adopts part or all of the technical solutions of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.
[0070] In some embodiments of the present application, the substrate is ITO conductive glass or FTO conductive glass; and / or,
[0071] The material of the electron transport layer includes SnO2, TiO2, C 60 , C 60 at least one of the derivatives; and / or,
[0072] The thickness of the electron transport layer is 10 to 50 nm; and / or,
[0073] The thickness of the perovskite layer is 300-800 nm; and / or,
[0074] The thickness of the passivation layer is 5 to 30 nm; and / or,
[0075] The material of the hole transport layer includes at least one of Spiro-Ometad, nickel oxide, copper oxide, and PTAA; and / or,
[0076] The thickness of the hole transport layer is 10 to 50 nm; and / or,
[0077] The material of the electrode includes at least one of Au, Ag and Cu.
[0078] It is easy to understand that ITO conductive glass refers to a soda-lime-based glass substrate or a borosilicate-based glass substrate with a layer of indium tin oxide (commonly known as ITO) film on the surface. FTO conductive glass is a transparent sheet material of SnO2 doped with fluorine. Spiro-Ometad is the common name for 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene. PTAA is the common name for polytriarylamine.
[0079] As an example, the thickness of the electron transport layer may be 10 nm, 20 nm, 30 nm, 40 nm, 50 nm. As an example, the thickness of the perovskite layer may be 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm. As an example, the thickness of the passivation layer may be 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm. As an example, the thickness of the hole transport layer may be 10 nm, 20 nm, 30 nm, 40 nm, 50 nm.
[0080] In some embodiments of the present application, the thickness of the electron transport layer is 20 to 40 nm; and / or,
[0081] The thickness of the passivation layer is 10 to 20 nm; and / or,
[0082] The thickness of the hole transport layer is 20-40 nm.
[0083] It is easy to understand that the beneficial effect of further limiting the thickness of the electron transport layer to 20-40 nm is that the thickness of 20-40 nm is not easy to produce tunneling effect, it is easy to fully cover the substrate, and the resistance to carrier transport is small, and the transmittance is also high.
[0084] As an example, the thickness of the electron transport layer may be 20 nm, 25 nm, 30 nm, 35 nm, or 40 nm.
[0085] It is easy to understand that the beneficial effect of the passivation layer having a thickness of 10 to 20 nm is that it is easy to completely cover and fully passivate the perovskite layer without generating a large resistance to carrier transport, and the transmittance is also high.
[0086] As an example, the thickness of the passivation layer may be 10 nm, 12 nm, 14 nm, 16 nm, 18 nm, or 20 nm.
[0087] It is easy to understand that the beneficial effect of the hole transport layer having a thickness of 20 to 40 nm is that the thickness of 20 to 40 nm is not easy to produce a tunneling effect, is easy to fully cover the substrate, and has less resistance to carrier transport.
[0088] As an example, the thickness of the hole transport layer may be 20 nm, 25 nm, 30 nm, 35 nm, or 40 nm.
[0089] In a third aspect, an embodiment of the present application provides a method for preparing a solar cell, the method comprising the following steps:
[0090] S1: providing a substrate;
[0091] S2: preparing an electron transport layer on the substrate;
[0092] S3: preparing a perovskite layer on the electron transport layer;
[0093] S4: coating a passivation solution on the perovskite layer, wherein the solute of the passivation solution includes 5-fluorobenzoxazole-2-thiol;
[0094] S5: performing a first heat treatment on the passivation solution on the perovskite layer so that the passivation solution forms a passivation layer;
[0095] S6: preparing a hole transport layer on the passivation layer,
[0096] S7: preparing an electrode on the hole transport layer to obtain the solar cell.
[0097] In some embodiments of the present application, step S2 prepares an electron transport layer on the substrate by spin coating, vapor deposition or coating.
[0098] In some embodiments of the present application, step S6 prepares an electron transport layer on the substrate by spin coating, vapor deposition or coating.
[0099] In some embodiments of the present application, the electrode is prepared by evaporation.
[0100] In some embodiments of the present application, the step of preparing a perovskite layer on the electron transport layer comprises the following steps:
[0101] S31: coating an inorganic salt solution on the electron transport layer;
[0102] S32: coating the organic salt solution on the inorganic salt solution;
[0103] S33: performing a second heat treatment on the inorganic salt solution and the organic salt solution so that the organic salt solution and the inorganic salt solution react to form a perovskite layer.
[0104] Wherein, the organic salt is at least one of FAI, MAI, MACl, FABr and MABr, and the inorganic salt is at least one of PbI2, PbBr2, PbCl2, CsBr, CsI and SnI2.
[0105] It is easy to understand that FAI is formamidine hydroiodide, MAI is methylammonium iodide, MACl is methylammonium chloride, FABr is formamidine hydrobromide, and MABr is methylammonium bromide.
[0106] In some embodiments of the present application, the temperature of the first heat treatment is 50-150° C.; and / or,
[0107] The first heat treatment lasts for 1 to 10 minutes; and / or,
[0108] The temperature of the second heat treatment is 100-150° C.; and / or,
[0109] The second heat treatment time is 10 to 15 minutes.
[0110] As an example, the temperature of the first heat treatment may be 50°C, 70°C, 100°C, 130°C, or 150°C.
[0111] As an example, the time of the first heat treatment can be 1 min, 2 min, 4 min, 6 min, 8 min, or 10 min.
[0112] As an example, the temperature of the second heat treatment may be 100°C, 110°C, 120°C, 130°C, 140°C, or 150°C.
[0113] As an example, the time of the second heat treatment can be 10 min, 11 min, 12 min, 13 min, 14 min, or 15 min.
[0114] In some embodiments of the present application, the temperature of the first heat treatment is 70-100° C.; and / or,
[0115] The first heat treatment time is 3 to 5 minutes.
[0116] It is easy to understand that the beneficial effect of the first heat treatment temperature being 70-100° C. is that it can fully promote the formation of the perovskite crystal phase and ensure the uniformity and stability of the perovskite layer.
[0117] As an example, the temperature of the first heat treatment may be 70°C, 80°C, 90°C, or 100°C.
[0118] It is easy to understand that the beneficial effect of the first heat treatment time of 3 to 5 minutes is that the perovskite crystal phase can be fully formed, and the first heat treatment time can be kept as short as possible, and the process efficiency is high.
[0119] As an example, the time of the first heat treatment can be 3 min, 3.5 min, 4 min, 4.5 min, or 5 min.
[0120] In some embodiments of the present application, the solvent of the passivation solution is isopropanol; and / or,
[0121] The concentration of 5-fluorobenzoxazole-2-thiol in the passivation solution is 0.5-5 mg / ml.
[0122] As an example, the concentration of 5-fluorobenzoxazole-2-thiol in the passivation solution may be 0.5 mg / ml, 1 mg / ml, 2 mg / ml, 3 mg / ml, 4 mg / ml, or 5 mg / ml.
[0123] In some embodiments of the present application, the concentration of 5-fluorobenzoxazole-2-thiol in the passivation solution is 0.5-2 mg / ml.
[0124] It is easy to understand that the beneficial effect of the concentration of 5-fluorobenzoxazole-2-thiol in the passivation solution being 0.5 to 2 mg / ml is that the passivation solution can be solidified faster under the conditions of the second heat treatment, and the distribution of 5-fluorobenzoxazole-2-thiol on the surface of the perovskite layer is more uniform.
[0125] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.
[0126] Example
[0127] This embodiment provides a perovskite solar cell, which is prepared by the following method:
[0128] Providing ITO conductive glass as a substrate, the ITO conductive glass comprising a glass substrate and an ITO film arranged on the surface of the glass substrate, the length and width of the ITO conductive glass are both 1.5 cm, the thickness of the glass substrate is 1 mm, and the thickness of the ITO film is 100 nm;
[0129] The ITO conductive glass was cleaned with ethanol, isopropanol and acetone for 30 minutes each, and then dried with a nitrogen gun;
[0130] Dilute 12% nano-tin dioxide dispersion with ultrapure water in a volume ratio of 1:3, and stir thoroughly to obtain a SnO2 dilution solution;
[0131] Take 40 μL SnO2 dilution and spread it evenly on the surface of ITO conductive glass. Spin coat it with a spin coater at a speed of 4000 rpm / s for 30 seconds.
[0132] After the SnO2 dilution solution was spin-coated, the ITO conductive glass was placed on a heating table at 150°C for annealing for 30 minutes to obtain a 20nm thick SnO2 film, i.e., the electron transport layer. The electron transport layer was placed in a UV ozone cleaning apparatus for 30 minutes.
[0133] Weigh 600 mg of lead iodide and 17 mg of cesium iodide and add them to a mixed solvent of 900 μL of N,N-dimethylformamide and 100 μL of dimethyl sulfoxide, heat and stir at 70°C to fully dissolve the lead iodide and cesium iodide to obtain an inorganic salt solution. Dissolve 110 mg of formamidine hydroiodide and 23.15 mg of methylammonium chloride in 1 mL of IPA solution and stir to fully dissolve them to obtain an organic salt solution.
[0134] Take 20 μL of inorganic salt solution and spread it evenly on the surface of the SnO2 film, and spin coat it with a spin coater, the spin coating speed is 2000 rpm / s, and the time is 50 s. At the 30th second, take 40 μL of organic salt solution and spread it evenly on the surface of the inorganic salt solution and continue to spin coat it;
[0135] After the organic salt solution is spin-coated, the ITO conductive glass is placed on a hot plate at 150° C. for annealing for 15 minutes, so that the organic salt solution and the inorganic salt solution react to form a 400 nm thick perovskite layer;
[0136] Weigh 1 mg of 5-fluorobenzoxazole-2-thiol and add it to 10 ml of isopropanol. -1 The mixture was stirred at a speed of 1 h to obtain a passivation solution;
[0137] 40 μl of the passivation solution was evenly spread on the surface of the perovskite layer, and spin-coated by a spin coater at a speed of 3000 rpm / s for 30 seconds. After the spin coating of the passivation solution was completed, the ITO conductive glass was placed on a hot plate at 70° C. and annealed for 5 minutes, so that the passivation solution formed a passivation layer;
[0138] 520 mg of bis(trifluoromethanesulfonyl)imide lithium salt (Li-TFSI) was weighed and dissolved in 1 mL of acetonitrile (ACN), and the mixture was stirred thoroughly to obtain solution A. Then 36.15 mg of 2,2,7,7-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9-spirobifluorene (Spiro-Ometad) was weighed and added into 1 mL of chlorobenzene, and the mixture was stirred thoroughly to obtain solution B; 8.75 μL of 4-tert-butylpyridine (TBP) solution and solution A were added into solution B, and the mixture was stirred thoroughly to obtain solution C;
[0139] Take 40 μL of solution C and spread it evenly on the surface of the passivation layer. Spin coat it with a spin coater at a speed of 4000 rpm / min for 30 s to form a 50 nm thick hole transport layer.
[0140] Transfer the ITO conductive glass to the thermal evaporation equipment, and the vacuum degree reaches 1×10 -5 Pa, an electrode (Ag) was evaporated on the surface of the hole transport layer with a thickness of 100 nm; it was then placed in an oxygen-filled glove box for 12 hours to obtain a perovskite solar cell.
[0141] Comparative Example
[0142] The difference between this comparative example and the embodiment is that no passivation layer is prepared. The details are as follows:
[0143] This comparative example provides a perovskite solar cell, which is prepared by the following method:
[0144] Providing ITO conductive glass as a substrate, the ITO conductive glass comprising a glass substrate and an ITO film arranged on the surface of the glass substrate, the length and width of the ITO conductive glass are both 1.5 cm, the thickness of the glass substrate is 1 mm, and the thickness of the ITO film is 100 nm;
[0145] The ITO conductive glass was cleaned with ethanol, isopropanol and acetone for 30 minutes each, and then dried with a nitrogen gun;
[0146] Dilute 12% nano-tin dioxide dispersion with ultrapure water in a volume ratio of 1:3, and stir thoroughly to obtain a SnO2 dilution solution;
[0147] Take 40 μL SnO2 dilution and spread it evenly on the surface of ITO conductive glass. Spin coat it with a spin coater at a speed of 4000 rpm / s for 30 seconds.
[0148] After the SnO2 dilution solution was spin-coated, the ITO conductive glass was placed on a heating table at 150°C for annealing for 30 minutes to obtain a 20nm thick SnO2 film, i.e., the electron transport layer. The electron transport layer was placed in a UV ozone cleaning apparatus for 30 minutes.
[0149] Weigh 600 mg of lead iodide and 17 mg of cesium iodide and add them to a mixed solvent of 900 μL of N,N-dimethylformamide and 100 μL of dimethyl sulfoxide, heat and stir at 70°C to fully dissolve the lead iodide and cesium iodide to obtain an inorganic salt solution. Dissolve 110 mg of formamidine hydroiodide and 23.15 mg of methylammonium chloride in 1 mL of IPA solution and stir to fully dissolve them to obtain an organic salt solution.
[0150] Take 20 μL of inorganic salt solution and spread it evenly on the surface of the SnO2 film, and spin coat it with a spin coater, the spin coating speed is 2000 rpm / s, and the time is 50 s. At the 30th second, take 40 μL of organic salt solution and spread it evenly on the surface of the inorganic salt solution and continue to spin coat it;
[0151] After the organic salt solution is spin-coated, the ITO conductive glass is placed on a hot plate at 150° C. for annealing for 15 minutes, so that the organic salt solution and the inorganic salt solution react to form a 400 nm thick perovskite layer;
[0152] 520 mg of bis(trifluoromethanesulfonyl)imide lithium salt (Li-TFSI) was weighed and dissolved in 1 mL of acetonitrile (ACN), and the mixture was stirred thoroughly to obtain solution A. Then 36.15 mg of 2,2,7,7-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9-spirobifluorene (Spiro-Ometad) was weighed and added into 1 mL of chlorobenzene, and the mixture was stirred thoroughly to obtain solution B; 8.75 μL of 4-tert-butylpyridine (TBP) solution and solution A were added into solution B, and the mixture was stirred thoroughly to obtain solution C;
[0153] Take 40 μL of solution C and spread it evenly on the surface of the perovskite layer. Spin-coat it with a spin coater at a speed of 4000 rpm / min for 30 s to form a 50 nm thick hole transport layer.
[0154] Transfer the ITO conductive glass to the thermal evaporation equipment, and the vacuum degree reaches 1×10 -5 Pa, an electrode (Ag) was evaporated on the surface of the hole transport layer with a thickness of 100 nm; it was then placed in an oxygen-filled glove box for 12 hours to obtain a perovskite solar cell.
[0155] Related experiments and effect data:
[0156] The current density-voltage (JV) curves of the batteries prepared in the examples and comparative examples were tested using the CME-IPCE photoelectrochemical test system. The test was completed on the Keysight 2400 system. The test conditions were: the simulated light intensity was 100 mW cm -2 (AM1.5G) scanning rate is 0.1Vs -1 (step size is 0.02V, time delay is 200ms), the scanning range is 1.2V to -0.2V, and the power output of the xenon lamp is calibrated by the NERL (National Renewable Energy Laboratory) standard KG5 standard Si battery. The test results are as follows Figure 1 , Figure 2 As shown, Figure 1 The voltage-current curve of the control group with 5-fluorobenzoxazole-2-thiol added. Figure 2 The box plot of battery performance between the battery with 5-fluorobenzothiol added and the control group.
[0157] Figure 1 The voltage-current curve of the control group with 5-fluorobenzoxazole-2-thiol added, the dotted line is the control group, and the solid line is the perovskite solar cell with thiol added. The figure shows that after adding thiol, the open circuit voltage and circuit current of the perovskite solar cell with thiol as a passivator are significantly improved compared with the perovskite solar cell without thiol. Correspondingly, the efficiency is also greatly improved. Figure 2 The box plot of battery performance of the battery with 5-fluorobenzoxazole-2-thiol added and the control group is shown in Figure 2. Figure 2 (a) is the open circuit voltage, Figure 2 (b) is the short-circuit current density, Figure 2 (c) is the filling factor, Figure 2 (d) is the efficiency. It can be clearly seen from the figure that after adding thiol, the open circuit voltage distribution of the sub-cell is more concentrated, the short circuit current is significantly improved, and the change in the filling factor is not obvious. These performance changes lead to the improvement of efficiency, proving that thiol can effectively reduce and fill the surface defects of the perovskite layer and reduce the defect density of the perovskite layer.
[0158] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0159] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application specification, the terms "including", "comprising", etc. refer to "including but not limited to". Moreover, the terms "including", "comprising" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements not only includes those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of further restrictions, the elements defined by the sentence "including..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements. In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that there can be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. For the association relationship of more than three associated objects described by "and / or", it means that any one of these three associated objects can exist alone, or any at least two of them exist at the same time. For example, for A, and / or B, and / or C, it can be represented that any one of A, B, and C exists alone, or any two of them exist at the same time, or three of them exist at the same time. In this article, "at least one" refers to one or more, and "multiple" refers to two or more. "At least one", "the following at least one (individual)" or similar expressions refer to any combination of these items, including any combination of single items (individuals) or plural items (individuals). For example, "at least one (individual) of a, b, or c", or "at least one (individual) of a, b, and c", can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, wherein a, b, c can be single or multiple respectively. The "number of parts" involved in this application, such as weight parts, mass parts, etc., represent the proportional relationship between each component. In the proportional relationship involved in the present application, the parameters that need to be described by proportion should be understood as the first term of the proportional formula in the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, if the mass ratio of substance A, substance B and substance C is 1:2:3, then substance A, substance B and substance C should correspond one-to-one with the proportional numbers in the proportional formula in the order of description, that is, the mass of substance A: the mass of substance B: the mass of substance C = 1:2:3.
[0160] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. An application of 5-fluorobenzoxazole-2-thiol, characterized in that: The 5-fluorobenzoxazole-2-thiol is used as a passivator for a perovskite layer in a perovskite solar cell.
2. A solar cell, characterized in that: The solar cell comprises: substrate; An electron transport layer disposed on the substrate; a perovskite layer disposed on the electron transport layer; a passivation layer disposed on the perovskite layer; A hole transport layer is provided on the passivation layer, An electrode disposed on the hole transport layer, Wherein, the material of the passivation layer includes 5-fluorobenzoxazole-2-thiol.
3. The solar cell according to claim 2, characterized in that: The substrate is ITO conductive glass or FTO conductive glass; and / or, The material of the electron transport layer includes SnO2, TiO2, C 60 , C 60 at least one of the derivatives; and / or, The thickness of the electron transport layer is 10 to 50 nm; and / or, The thickness of the perovskite layer is 300-800 nm; and / or, The thickness of the passivation layer is 5 to 30 nm; and / or, The material of the hole transport layer includes at least one of Spiro-Ometad, nickel oxide, copper oxide, and PTAA; and / or, The thickness of the hole transport layer is 10 to 50 nm; and / or, The material of the electrode includes at least one of Au, Ag and Cu.
4. The solar cell according to claim 3, characterized in that: The thickness of the electron transport layer is 20 to 40 nm; and / or, The thickness of the passivation layer is 10 to 20 nm; and / or, The thickness of the hole transport layer is 20-40 nm.
5. A method for preparing a solar cell, characterized in that: The method comprises the following steps: providing a substrate; preparing an electron transport layer on the substrate; preparing a perovskite layer on the electron transport layer; coating a passivation solution on the perovskite layer, wherein the solute of the passivation solution includes 5-fluorobenzoxazole-2-thiol; Performing a first heat treatment on the passivation solution on the perovskite layer so that the passivation solution forms a passivation layer; preparing a hole transport layer on the passivation layer, An electrode is prepared on the hole transport layer to obtain the solar cell.
6. The method for preparing a solar cell according to claim 5, characterized in that: The method of preparing a perovskite layer on the electron transport layer comprises the following steps: coating an inorganic salt solution on the electron transport layer; coating an organic salt solution on the inorganic salt solution; The inorganic salt solution and the organic salt solution are subjected to a second heat treatment so that the organic salt solution and the inorganic salt solution react to form a perovskite layer. Wherein, the organic salt is at least one of FAI, MAI, MACl, FABr and MABr, and the inorganic salt is at least one of PbI2, PbBr2, PbCl2, CsBr, CsI and SnI2.
7. The method for preparing a solar cell according to claim 5, characterized in that: The temperature of the first heat treatment is 50-150° C.; and / or, The first heat treatment lasts for 1 to 10 minutes; and / or, The temperature of the second heat treatment is 100-150° C.; and / or, The second heat treatment time is 10 to 15 minutes.
8. The method for preparing a solar cell according to claim 7, characterized in that: The temperature of the first heat treatment is 70-100° C.; and / or, The first heat treatment time is 3 to 5 minutes.
9. The method for preparing a solar cell according to claim 5, characterized in that: The solvent of the passivation solution is isopropanol; and / or, The concentration of 5-fluorobenzoxazole-2-thiol in the passivation solution is 0.5-5 mg / ml.
10. The method for preparing a solar cell according to claim 9, characterized in that: The concentration of 5-fluorobenzoxazole-2-thiol in the passivation solution is 0.5-2 mg / ml.